PENGARUH WAKTU KONTAK DAN UKURAN ADSORBEN TERHADAP PEMURNIAN BIOETANOL DARI KULIT NANAS - Setyawati, Harimbi; Rahman, Nanik Astuti; -, Solekah (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
The use of food as an alternative feedstock fuels, bioethanol, can threaten food security if not done wisely in its management. To cope with that then developed the fermentation of food waste that still contain carbohydrates, in this study used pineapple rinds juice as raw material for bioethanol. Ethanol produced still contains a little ethanol, despite the rise of distilled ethanol does not increase levels of purification process that takes another alternative, namely adsorption. Adsorbent used is a synthetic zeolite. From the results showed that the adsorption process can be increased ethanol content.